Awareness and involvement of downstream residents toward the mitigation plan of Dam failure: a case study of Klang Gate Dam - Ibrahim, Illyani; Ghazali, Ahmad Aiman; Jaafar, Samsuddin; Mahamod, Lukman Hakim (American Scientific Publishers, 2017)
Dam planning development is important to provide water source to human and the environment. However, this development also poses a huge risk in the case of dam failure caused by natural disasters or operational failures. As part of the development of a dam, a mitigation plan should be provided to analyze the impact and provide the escape plan for the public residing in the risk areas. Hence, the public should be involved in the preparation of the mitigation plan to ensure the effectiveness of the plan. The current study seeks to determine the level of awareness and involvement of the public, especially the downstream residents in the preparation of the mitigation plan. This study also discusses the dam development planning in relation to dam failure and public involvement. A survey was done to investigate the level of awareness and involvement of the downstream residents in the chosen area towards the mitigation plan of dam failure. The major findings are hoped to guide in identifying the appropriate tools to improve the awareness of downstream residents in facing emergency situations resulting from dam failures.